The Superiority of Supercritical Fluid Extraction Over Steam Distillation and Solvent Extraction Methods for the Extraction of Aroma from Salacca zalacca (Gaertn.) Voss - Mohd Mokhlesur, Rahman; Hafizan, Juahir; Tengku Mohammad Ariff, Raja Hussin (2019)
Salacca zalacca (Gaertn.) Voss or snake fruit is a species of palm tree native to Southwest Java and North Sumatra in Indonesia. It is known as one of the exotic fruits in Malaysia. It has a pleasant pineapple, pear and banana-like aromas. Due to its pleasant aroma, Salacca zalacca has potential in the perfumery and pharmaceutical industries. New extraction techniques were introduced in this study to overcome conventional methods limitations such as supercritical fluid extraction (SFE). This technique is available to extract aroma of plants and it is rapidly gaining attention due to its superior benefits over the conventional extraction methods. In this study, the volatile aroma of Salacca zalacca was extracted by steam distillation, solvents extraction with hexane, diethyl ether and dichloromethane (DCM) and SFE. Carbon dioxide was the supercritical fluid for the SFE. The efficiency and percentage yield of these extracts were compared. The percentage Yields of SFE extracts were higher (10 MPa, 30°C: 0.2577 %; 25 MPa, 30°C: 0.2375 %; 30 MPa, 30°C: 0.2721 %) than the steam distillation (0.1855 %), diethyl ether (0.5692 %), hexane (0.0511 %) and DCM (0.1358 %) solvent extracts. However, SFE produced a lower yield (40 MPa, 70°C: 0.2721 %) than the diethyl ether solvent extraction (0.5692 %) but SFE was found to be more efficient and environmentally friendly.